Hidden Heroes : America's Military Caregivers - Rajeev Ramchand (RAND Corporation, 2013)
Many wounded, injured, or disabled veterans rely for their day to day care on informal caregivers: family members, friends, or acquaintances who devote substantial amounts of time and effort to caring for them. These informal caregivers, who we term military caregivers, play a vital role in facilitating the recovery, rehabilitation, and reintegration of wounded, ill, and injured veterans. The assistance provided by caregivers saves the United States millions of dollars each year in health care costs and allows millions of veterans to live at home rather than in institutions. Yet the toll of providing this care can be high. A preliminary phase of our research commissioned by Caring for Military Families: The Elizabeth Dole Foundation (Military Caregivers: Cornerstones of Support for Our Nation’s Wounded, Ill, and Injured Veterans, Tanielian et al., 2013) found that time spent caregiving can lead to the loss of income, jobs, or health care and exact a substantial physical and emotional toll. To the extent that caregivers’ well-being is compromised, they may become unable to fulfill their caregiving role, leaving the responsibilities to be borne by other parts of society. Most of this prior research focused on caregivers in general, with little evidence about the impact of caregiving on military caregivers specifically. In recognition of their growing number, particularly in the wake of the conflicts in Iraq and Afghanistan, it has become paramount to understand the support needs of military caregivers and the extent to which available resources align with those needs. This report presents results from the second phase of our analysis